Development of High-Temperature Ranking Parameter for Asphalt Binders Using Arrhenius Model - Saboo N.; Singh B.; Kumar P. (My University, 2025)
Developing appropriate experiments to characterize the rutting potential of an asphalt binder will aid in suitable selection of asphalt binders for a location, depending on the prevailing temperature and loading conditions. This study is an attempt to develop a ranking parameter for the high-temperature performance of asphalt binders that can explain the effect of temperature, stress levels, and short-term aging. Six different asphalt binders comprising conventional, warm mix modified, and polymer modified binders were used in the study. A multiple stress creep and recovery (MSCR) test was conducted at 40°C, 50°C, 60°C, and 70°C using four different stress levels of 3.2, 5, 8, and 10 kPa. The test was conducted on unaged and rolling thin-film oven (RTFO) aged conditions. The Arrhenius equation was used to model the variation of unrecoverable creep compliance, Jnr, with temperature at different stress levels. It was found that, irrespective of stress level and aging condition, the Arrhenius equation can be successfully used to model the variation of Jnr with temperature. The activation energy, Ea, in the Arrhenius equation was found to be a useful parameter to explain the rutting characteristics of the asphalt binders. A new ranking parameter Eā/(Jąnr,Maximum Temperature×mą) was defined in the study and it can be successfully used to quantify the high-temperature performance of asphalt binders. An aging index was also proposed using the ranking parameter to explain the effect of short-term aging on the rutting susceptibility of the binders. The comparative analysis of the asphalt binders led to a conclusion that elastomeric polymer modified binder, PMB-S, outperforms all the other asphalt binders in both unaged and aged conditions. It is envisaged that such ranking system will ensure the true behavior of asphalt binders under variation of temperature and load conditions in the pavement. © 2019 American Society of Civil Engineers.